Life-threatening retroperitoneal hematoma after percutaneous vertebroplasty for lumbar fracture - Aleixo, Catarina; Marinhas, Jose; Santos, Filipe; Freitas, Rolando; Pereira, Ricardo Santos (International Journal of Research in Orthopaedics, 2020)
Percutaneous vertebroplasty is a safe and effective minimally invasive procedure with specific potential complications. Among these, vascular injuries have seldomly been reported. We present a rare case of retroperitoneal hematoma, presumably from injury to one of the lumbar arteries following percutaneous vertebroplasty in a patient treated for lumbar fracture. Even though the situation was life-threatening, conservative treatment and support measures sufficed in controlling the bleeding and the patient recovered fully. Spine surgeons should be especially aware of this specific and often late-presenting complication, as early recognition and prompt treatment are fundamental to decrease its morbidity and mortality.